To solve for d, we need to isolate the variable on one side of the equation. Let's begin by adding 13/2 to both sides:
6d - 11/2 + 13/2 = 2d - 13/2 + 13/2
6d + 2/2 = 2d
6d + 1 = 2d
Next, let's subtract 2d from both sides:
6d - 2d + 1 = 2d - 2d
4d + 1 = 0
To isolate d, let's subtract 1 from both sides:
4d + 1 - 1 = 0 - 1
4d = -1
Finally, to solve for d, we divide both sides by 4:
4d/4 = -1/4
d = -1/4
Therefore, the value of d that solves the equation is d = -1/4.
Solve for d
6d - 11/2 = 2d - 13/2
1 answer